Extensive gastric necrosis in an infant - Gandhi, Suraj R.; Shenoy, Neha S.; Joseph, Vini; Makan, Apoorva P.; Basu, Syamantak; Tulsian, Akriti R.; Shah, Hemanshi S. (International Surgery Journal, 2021)
Gastric necrosis is a rare condition, more so in children and can be potentially fatal. The sloughing of the necrosed wall results in perforations or large defects in the gastric wall. We report a rare case of extensive gastric necrosis in a 2 months old female infant, managed successfully. Child presented with non-bilious vomiting and excessive cry. There was history of recurrent upper abdominal distension. X-ray of abdomen showed massive pneumoperitoneum. Intra operatively, posterior gastric wall was sloughed off and lower end of feeding tube was lying in the peritoneal cavity. Necrotic wall was debrided and stomach tube was created from remaining anterior gastric wall. Gastrostomy and jejunostomy was done. Post-operative period was uneventful. Dye study at three months showed good gastric capacity. Stomach being a well vascularised organ, necrosis is rare. There is varied etiology of gastric necrosis, volvulus being one of them. Gastric volvulus might be associated with other congenital anomalies like eventration, asplenia, wandering spleen. The incidence of perforation in gastric volvulus with necrosis is 5-28% and a mortality of 50% is reported with such perforations. Vigilant clinical observation in pediatric patients with upper abdominal distension and pain can point the diagnosis and prevent fatal outcome.